Extreme Poverty and Food Insecurity as sources of Entrepreneurial Orientation among Food Traders in a Rural Community of Chisamba - Mudenda, Collins; Simate, Isaac N; Chileshe, Mwape (Journal of Contemporary Research in Management (JCRM), 2023)
The study was conducted in order to establish if poverty and food insecurity can be sources of entrepreneurial orientation among food traders. Poverty and food insecurity represent the two major challenges faced many communities, for which the United Nations target to eradicate poverty and eliminate hunger as envisioned in the Sustainable Development Goals (SDGs). The study was conducted using a mixed research design were both qualitative and quantitative data were collected. A structured questionnaire was used to collect data, and was prepared using the Food Insecurity Experience Scale (FIES). Data were collected from 95 food traders, utilizing a census approach. Data were analysed using descriptive statistical functions such as means and frequencies as well as arithmetic calculations. The results indicate that all the respondents live in extreme poverty, measured through cut-off line of living under US $2.15 per person per day. Specifically, 40.6% live under US $0.81, 23% live under US $1.81 and 15% live under US $1.35. Further, the respondents eat a variety of food stuff as and when available but were still food insecure because they usually eat same type of food, adults and children skip meals and have reduced food portions when food is available, food doesn’t last and it runs out often. Therefore, the households are forced to engage in farming so as to produce food crop for home consumption and sale the excess at designated trading areas and roadside markets. The respondents were found to exhibit entrepreneurial orientation characteristics of competitiveness, aggression, proactivity and autonomy. Based on this finding, it can be concluded that poverty and food insecurity are a source of entrepreneurial orientation